Recovery of zinc from copper smelter slag by sulfuric acid leaching in an aqueous and alcoholic environment - Turan, M. D.; Karamyrzayev, G. A.; Nadirov, R. K. (Al-Farabi Kazakh Natl Univ, 2021)
The content of zinc in copper smelter slags obtained from pyrometallurgical copper production is comparable to the content of this metal in zinc ores. Therefore, these slags are considered a valuable secondary resource for zinc recovery. At the same time, the features of the mineralogical composition of the slag make the extraction of zinc from it very problematic. Most of the zinc is concentrated in the refractory zinc ferrite (ZnFe2O4). To avoid the formation of a viscous pulp when leaching copper smelter slag with an aqueous solution of sulfuric acid, in this work, the slag was leached with sulfuric acid also in isopropanol and n-pentanol, under the following conditions: 0.5 M H2SO4, pulp density 50 g/L, magnetic stirrer rotation speed 600 rpm. The influence of the duration and temperature of leaching milled (<= 100 mu m) copper smelter slag of the Balkhash copper smelter on the extraction of zinc into solution was investigated. It was found that the maximum zinc recovery into an aqueous solution was 75 +/- 2% at 363 K and 210 min. Replacing water with isopropanol or n-pentanol led to an increase in zinc recovery to 82 +/- 2% at 210 min and a lower temperature (353 K) than in an aqueous environment. An increase in temperature to 383 K during leaching in n-pentanol made it possible to extract 92 +/- 2% of zinc. A shrinking core model was used to describe the kinetics of the zinc leaching process. It was found that the limiting stage of the process under all investigated conditions is the chemical leaching reaction. Some kinetic characteristics of the leaching process were calculated, in particular, the apparent reaction rate constants, as well as the activation energy.
Keywords: copper smelter slag; leaching; zinc recovery; isopropanol; n-pentanol